Reduction of biofouling in paper production processes by using a carbamate-based biocide as a retention agent - Pereira, Maria Olívia (2001)
The paper focuses on biofilm development in pulp and paper mills. A carbamate-based biocide was used to modify the surface properties of the microbial cells in order to promote their attachment to the cellulose fibres and to prevent the bacteria from developing biofilms on the equipment. About 75% of the cells were retained by the fibres. The effect of glutaraldehyde, another traditional biocide in pulp mills, was also tested and it was concluded that this biocide did not modify the surface charge of the bacteria.